A h-BCN for Electrochemical Sensor of Dopamine and Uric Acid. (16th January 2020) - Bi, Yun-Shuai; Liu, Bo; Liu, Xu-Ying; Qin, Ying; Zou, Ben-Xue
Abstract : A hexagonal boron carbon nitride hybrid (h-BCN) is developed by in situ high-temperature solid-state reaction and subsequent chemical reduction with hydrazine. The XRD and TEM results show that the h-BCN features interlayered structures with two characteristic d -spacing of 0.33 and 0.21 nm. The obtained h-BCN exhibits significant electrochemical sensor for dopamine and uric acid. The cyclic voltammetric and amperometric experiments revealed a good linear relationship between current densities and concentrations of dopamine (DA) of 10-300 μ M and uric acid (UA) of 10-500 μ M, with high sensitivities of 0.14 μ A/ μ M and 0.32 μ A/ μ M and detection limits of 5 μ M and 2 μ M, respectively.